INFLUENCE OF ROTATING SAVINGS AND CREDIT ASSOCIATIONS SERVICES ON FINANCIAL PERFORMANCE OF MICRO AND SMALL ENTERPRISES: A CASE STUDY OF WOMEN OWNED MICRO AND SMALL ENTERPRISES IN NAKURU, KENYA - JEPKOMEN, KIBOWEN BRIDGID (KABARAK UNIVERSITY, 2024)
Women-owned micro and small enterprises face significant challenges in achieving optimal financial performance. Despite their vital role in the economy, these businesses encounter various obstacles that hinder their growth and sustainability. This study sought to assess the influence of rotating savings and credit association’s services on financial performance of women owned micro and small enterprises in Nakuru, Kenya. Specifically, the study sought to assess the savings contributions, credit facilities, emergency insurance services and support services on financial performance of women owned enterprises in Nakuru, Kenya. The study was anchored on financial inclusion theory, Trade-off theory, Resilience theory and social capital theory. The study used a descriptive research design. The population of the study comprised 682 Micro and small enterprises that are owned by women entrepreneurs in Rongai Sub-County, Njoro SubCounty and Bahati Sub- County. This study used a systematic random sampling to select those women who participate in Rotating Savings and Credit Associations. The sample size of 252 business women was obtained using Yamane, formula. Data was collected using structured questionnaires. A pilot study was conducted in Kericho County. Both face and content validity were assessed. An internal consistency technique was adopted to measure reliability of research instruments. All the variables had Cronbach overall value of 0.863 which was greater than 0.7. Quantitative analysis was used to analyze descriptive statistics. The findings revealed there exists a positive and significant relationship between savings contributions on the financial performance of womenowned enterprises in Nakuru, Kenya (r = .606, p=0.000). The findings further revealed that there is a strong, positive and statistically significant relationship between emergency insurance services on financial performance of women owned enterprises in Nakuru, Kenya (r=0.477, p=0.000). The findings also revealed that there is a strong, positive and statistically significant relationship between emergency insurance services on financial performance of women owned enterprises in Nakuru, Kenya (r=0.776, p=0.000). Finally the findings revealed that there exist a strong, positive and significant relationship between support services on financial performance of women owned enterprises in Nakuru, Kenya (r=0.763, p=0.000). From the findings the study concluded that saving contributions have a statistically significant influence on financial performance of women enterprises in Nakuru, Kenya. In addition the study concluded that credit facilities have statistically significant influence on financial performance of women enterprises in Nakuru, Kenya. Furthermore, the study concluded that emergency insurance services have statistically significant influence on financial performance of women enterprises in Nakuru, Kenya. Finally, the study concluded that support services have no statistically significant influence on the financial performance of women enterprises in Nakuru, Kenya. From the findings, the study recommends that ROSCA should encourage a culture of regular savings by promoting consistent contributions among members. They should also provide opportunities for members to build their creditworthiness within the ROSCA and explore partnerships with formal financial institutions to facilitate access to additional credit options
Keywords: INFLUENCE OF ROTATING SAVINGS AND CREDIT ASSOCIATIONS SERVICES ON FINANCIAL PERFORMANCE OF MICRO AND SMALL ENTERPRISES: A CASE STUDY OF WOMEN OWNED MICRO AND SMALL ENTERPRISES IN NAKURU, KENYA